Making better coffee : how Maya farmers and Third Wave tastemakers create value - Fischer, Edward F., 1966- (University of California Press, 2022)
"This book takes a behind-the-scenes look at the world of Third Wave coffee to uncover what makes a great coffee. Traders stress the material conditions of terroir and botany, but just as important are the social, moral, and political values that farmers, roasters, and consumers attach to the beans. Third Wave roasters earnestly pursue a craft, searching for new flavors, while smallholding Maya farmers in Guatemala see coffee as part of a cycle of agricultural regeneration, as well as a source of extra income. This book connects the quest for quality among Third Wave tastemakers in the United States to the lives and internet-fueled aspirations of Maya producers, showing how profits are made by artfully combining coffee's material and symbolic qualities"--